Atención al usuario y su incidencia en el nivel de satisfacción del Gobierno Autónomo Descentralizado Parroquial Rural Caracol, periodo 2024. - Heleno Bone, Jonathan Jordán (2024)
This research is carried out within the Caracol Rural Parochial Decentralized Autonomous Government, with the objective of analyzing the user care process that has been carried out during the 2024 period, in order to determine the degree of community satisfaction and that will allow identifying and proposing strategies to improve the quality of user care in a key public institution for the development of the Caracol community. The objective of the research was based on analyzing the impact of user care on the level of satisfaction of the community managed by the Caracol Rural Parochial Decentralized Autonomous Government, during the 2024 period, to propose effective citizen care strategies. The research modality was mixed (qualitative-quantitative), because theoretical foundations of the main variables under study were exposed and data obtained from the established population and/or sample were also detailed. The results of the study show that user care has a significant impact on the level of satisfaction of the community managed by the Caracol Rural Parochial GAD. The positive correlation obtained using the Spearman test confirms that better quality of care is directly related to greater user satisfaction.